The New Role of Biomedical Informatics in the Age of Digital Medicine - Martin-Sanchez, Fernando J.; Lopez-Campos, Guillermo H. (Methods of Information in Medicine, 2016)
Objectives: To reflect on the recent rise of Digital Medicine, as well as to analyse main research opportunities in this area. Through the use of several examples, this article aims to highlight the new role that Biomedical Informatics (BMI) can play to facilitate progress in research fields such as participatory and precision medicine. This paper also examines the potential impact and associated risks for BMI due to the development of digital medicine and other recent trends. Lastly, possible strategies to place BMI in a better position to face these challenges are suggested. Methods: The core content of this article is based on a recent invited keynote lecture delivered by one of the authors (Martin- Sanchez) at the Medical Informatics Europe conference (MIE 2015) held in Madrid in May 2015. Both authors (Lopez-Campos and Martin-Sanchez) have collaborated during the last four years in projects such as the ones described in section 3 and have also worked in reviewing relevant articles and initiatives to prepare this talk. Results and Conclusions: Challenges for BMI posed by the rise of technologically driven fields such as Digital Medicine are explored. New opportunities for BMI, in the context of two main avenues for biomedical and clinical research (participatory and precision medicine) are also emphasised. Several examples of current research illustrate that BMI plays a key role in the new area of Digital Medicine. Embracing these opportunities will allow academic groups in BMI to maintain their leadership, identify new research funding opportunities and design new educational programs to train the next genera -tion of BMI scientists.
Keywords: Biomedical informatics; digital medicine; participatory medicine; precision medicine; social media; self-quantification; exposome